Urgency and emergency in times of COVID-19 – an integrative literature review (Research, Society and Development, 2021)
This study aims to analyze the changes that occurred in urgent and emergency hospital care during the COVID-19 pandemic and to develop strategies to prevent the risks of health services collapse. This is an integrative review of the literature, with scientific studies being searched between the months of September and October 2020, in the databases PubMed, Virtual Health Library of the Ministry of Health and Google Scholar, with the descriptors "attendance", "emergency", “COVID-19” and “pandemic”. 689 articles were found in the three databases and 28 studies were selected that addressed the topic discussed, for the preparation of the review, in English, Portuguese and Spanish. The studies brought information about the epidemiological changes in the urgency and emergency departments, showing a new profile of care, showing the form and strategies that the epicenters of the pandemic in the world and Brazil have organized. It is noteworthy that through the scientific literature it was possible to identify the main changes that occurred in urgent and emergency care, in addition to adaptations in the hospital sectors and in the creation of new outpatient clinics to reduce the overload of health services, consequently, preventing their collapse.